Aloe uigensis (Asphodelaceae subfam. Alooideae), a new species from northwestern Angola - Smith, Gideon F.; Lautenschläger, Thea (Phytotaxa, 2021)
A new species of Aloe, A. uigensis (Asphodelaceae subfam. Alooideae), is described from northwestern Angola. It is a non-proliferous, single-stemmed species that bears narrowly elongated, acuminate racemes with orange to pale reddish flowers. Aloe uigensis is compared to some long-known as well as recently described species of Aloe from Angola, but does not have close relatives with which it can be confused in the country.